Zinc Intake and Appetite in Patients with Post-Tuberculosis Lung Disease at Persahabatan National Respiratory Referral Hospital, Jakarta - Mahardhika, Linda; Nurwidya, Fariz; Singal, Anna Maurina; Sutanto, Krisadelfa; Imaniar, Rania; Syam, Shaogi (Jurnal Respirasi, 2025)
Introduction: After completion of pulmonary tuberculosis (TB) treatment, some people may continue to experience respiratory issues that can progress into post-TB lung disease (PTLD). Individuals with PTLD exhibit suboptimal nutritional status. The loss of appetite is a significant factor influencing nutritional status. Zinc plays a role in hunger control.  Lack of zinc reduces taste sensitivity and food intake. This study examined the relationship between zinc intake and appetite in patients with PTLD at Persahabatan National Respiratory Referral Hospital, Jakarta. Methods: This cross-sectional study was conducted at Persahabatan National Respiratory Referral Hospital, Jakarta, from November 2024 to March 2025. Eighty-five adult patients with PTLD were included. Zinc intake was assessed by a semi-quantitative food frequency questionnaire (SQ-FFQ) and analyzed by NutriSurvey software. Appetite was measured using the visual analog scale (VAS) for appetite. Results: A total of 85 subjects participated in the study, comprising 78.8% males and 21.2% females. The average daily zinc intake was 4.4 mg/day, and 92.9% of the subjects had zinc intake below the recommended dietary allowance (RDA). The average VAS appetite score was 70 mm. A significant positive correlation was found between zinc intake and appetite, indicating that a decrease in zinc intake might result in a reduced appetite (r=0.266, p=0.014). Conclusion: Zinc intake is positively associated with appetite in patients with PTLD. Therefore, zinc intake monitoring is essential for supporting nutritional recovery and lung function in PTLD.